Influence of production and conservation conditions on some physical and chemical properties of blueberries - Gonçalves, Christophe (2017)
This work studied the effect of production mode (organic versus conventional) and storage conditions on some physical and chemical properties of blueberry from different cultivars, namely Duke, Bluecrop, and Ozarkblue. The physical properties evaluated were caliber, color and texture and the chemical characteristics analyzed were moisture content, total soluble solids and acidity. Furthermore, the effect of storage on these properties was also evaluated. The results showed that blueberries cultivar Duke was bigger, with a more intense coloration, and presented a harder and more elastic texture, when compared with the other cultivars at study. With respect to production mode, it was found that the blueberries produced in organic farming were not so acid or sweet, but had a more intense blue color. The storage conditions did not show an important influence on the chemical properties of blueberry, but influenced the both color and texture.